2022
DOI: 10.1017/s0950268822000255
|View full text |Cite
|
Sign up to set email alerts
|

Trust in the scientific research community predicts intent to comply with COVID-19 prevention measures: An analysis of a large-scale international survey dataset

Abstract: In the present study, I explored the relationship between people's trust in different agents related to prevention of spread of COVID-19 and their compliance with pharmaceutical and nonpharmaceutical preventive measures. The COVIDiSTRESSII Global Survey dataset, which was collected from international samples, was analysed to examine the aforementioned relationship across different countries. For data-driven exploration, network analysis and Bayesian generalized linear model (GLM) analysis were performed. The r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Specifically, doubters and deniers of COVID-19 risk tended to believe conspiracy theories related to the pandemic, expressed anti-elitist sentiments and reported low compliance with measures to reduce the spread of the virus [ 12 ]. Low trust in institutions, including the scientific community, is also linked to vaccine hesitancy as well as compliance with preventive measures in general [ 15 17 ]. Finally, conspiracy theories and negative attitudes towards experts have other detrimental effects such as increasing uncertainty and discrimination against marginalised groups [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, doubters and deniers of COVID-19 risk tended to believe conspiracy theories related to the pandemic, expressed anti-elitist sentiments and reported low compliance with measures to reduce the spread of the virus [ 12 ]. Low trust in institutions, including the scientific community, is also linked to vaccine hesitancy as well as compliance with preventive measures in general [ 15 17 ]. Finally, conspiracy theories and negative attitudes towards experts have other detrimental effects such as increasing uncertainty and discrimination against marginalised groups [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of scalar invariance, which assumes the same factor loadings and intercepts across groups, is essential to assure the quality of cross-national research using the scales [ 29 ]. Measurement alignment was performed to address the potential issue of measurement non-invariance reported by the measurement invariance test as done in prior COVID-19-related international survey studies if needed [ 15 ]. The measurement alignment process was expected to address non-invariance so that researchers would be able to conduct cross-national comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Monte Carlo simulations (on randomly generated datasets with 500 iterations each; N1 = 100, N2= 200, N3 = 500) were also performed to test whether alignment was completed in a reliable and consistent manner. In this process, the correlation coefficients between factor means and factor variances, obtained from MG-CFA and multigroup alignment, R 2 loadings and R 2 intercepts, respectively, were examined (values higher than .95 were considered satisfactory, Han et al, 2022).…”
Section: Analytical Strategymentioning
confidence: 99%
“…For H2 and H3, items from SF-MFQ and Trust in Institutions were entered into models individually instead of one composed score reflecting the underlying latent construct. To reduce the complexity of the models, we performed Bayesian Generalised Linear Model (GLM) before MLM to identify which indicators should be included in the models by comparing all possible models with predictors of interest including country as a random effect (Han, 2022). The decision was made by exploring which model demonstrated the highest BF from Bayesian GLM.…”
Section: Analytical Strategymentioning
confidence: 99%
“…At the same time, even though trust is defined and measured in a variety of different ways, studies conducted across multiple different populations have identified associations between trust in science and intention to get vaccinated or boosted for COVID-19 [8][9][10][11][12], as well as adherence to other measures to mitigate harm from the pandemic (eg, nonpharmaceutical interventions) [13][14][15][16][17]. Thus, even if the exact nature of the relationship is unclear, it is reasonable to speculate that trust in science and scientists is associated with people's behaviors during a public health emergency such as COVID-19.…”
Section: Trust In Science and Scientistsmentioning
confidence: 99%